Sôbre a ecologia da Selaginella sellowii Hieron - Potsch, Sylvio; Arens, Karl (Lilloa, 2021)
Selaginella sellowii Hieron. was examined as representant of xerophytic flora, on the naked rocks of gneiss in Rio de Janeiro and its environs. The leaf of this Selaginella presents a hygroscopic movement different from that of the known Selaginella of the S. lepidophylla type: The leaves close round the stems (Fig. 2) and curl in like the grass leaves (Fig. 10). The hygroscopic mechanism and the concerning anatomy of the leaf were studied and found to be limited. to a special tissue at the base of the leaf (Fig. 9). The leaf when completely dried, lost its dark green color passing to a greyish aspect due to the appearing of air in the epidermis cells. The rolling is due to the failure of contracture in the epidermis because of the formation of air spaces within them, where the underlying tissue contracts. The hygroscopic mechanism is independent of life and can be provoced by concentrated solutions of osmotic values close to 100 atmospheres. The absorption of water by the dry leaf is very quick (table 11). The loss of water (table 12) can go to 7% only in the air dry stage. The ecologic adaptation of Selaginella is discussed.